Collaborated nanosecond lasers processing of crude graphene oxide for superior supercapacitive performance. (April 2023) - Abd Elhamid, Abd Elhamid M.; Shawkey, Heba; Khalil, Ahmed A.I.; Azzouz, Iftitan M.
Abstract: Laser processing of supercapacitor electrodes is a simple, accurate and fast method for planner, binder-free and flexible devices fabrication. In this context, two nanosecond lasers of 355 and 1064 nm were applied to process graphene oxide separately in a single step and successively in subsequent two step. The injection of Ar gas during laser writing enables maximum reduction with a minimal thinning effect. Energy Dispersive X-ray spectroscopy (EDX) measurement showed a high reduction degree and oxygen contents of nearly zero due to high deposited laser power and induced plasma for the 1064 nm laser. Moreover, two step laser writing promoted a highly crystalline layered graphene despite the applied ambient conditions. The electrochemical characterization was applied via 2 and 3-electrodes setup in H2 SO4 (1 M) electrolyte, laser-induced graphene (LIG) electrodes achieved 633.3 and 345.5 mF/cm 2 at 0.5 and 5 mA/cm 2, respectively. Besides, energy and power densities of about 88 μWh/cm 2 (at 0.5 mA/cm 2 ) and 2500 μW/cm 2 (at 5 mA/cm 2 ), respectively. These values are several orders of magnitudes higher than previous reports of laser-processed crude graphene thanks to nanosecond laser interactions. The retention of capacitance was 114 % after 2000 cycles due to H2 SO4 electrolyte doping process. In addition, different laser processing interactions and subsequent application impact on electrochemical performance were studied. LIG samples were examined via scanning electron microscopy, EDX, Raman spectroscopy and x-ray diffraction, Brunauer–Emmett–Teller, high-resolution transmission electron microscope. This LIG's outstanding electrochemical performance will enable near-battery energy values when considering a faradic additive. Graphical abstract: Unlabelled Image Highlights: Very high areal capacitance for LIG electrode of 549.6 mF/cm2. Higley crystalline LIG using incorporated two lasers for writing processing. Re-oxidation and defect formation induced by second step laser wavelength. Second step laser processing induced back deposition of carbon nanoparticles on LIG sheets. Ar gas injection enables deposition of high power with minimal film thinning.